REALISASI PENGGUNAAN ALOKASI DANA DESA UNTUK PEMBANGUNAN DESA DI KECAMATAN TELAGA BIRU KABUPATEN GORONTALO (Studi Kasus di Desa Pentadio Timur) - Joice Machmud (Universitas Muhammadiyah Gorontalo, 2021)
This research aims to: determine the extent to which the Realization of Village Fund Allocation Utilization for Village Development in Telaga Biru sub-District, Gorontalo Regency (Case Study in East Pentadio Village). The research method uses a qualitative research approach with a descriptive type of research. The results found that: 1) Village Fund Allocation (ADD) received by the East Pentadio Village Government, Telaga Biru District, Gorontalo Regency was more directed at personnel expenditures, goods and services expenditures and capital expenditures, 2) Utilization of ADD funds on personnel expenditures to finance the fixed income of the village head and village apparatus, allowances for the village head and village apparatus as well as allowances for the BPD and its members, 3) The use of ADD funds in spending on goods and services is more directed towards fulfilling administrative matters, monthly fixed costs as well as official travel and others, and 4) Utilization of ADD funds in capital expenditures is more directed at activities for the acquisition of land and buildings as well as the procurement of office equipment. Keywords: ADD, Usage, Realization